Putting our money where our mouth is? The degree of women-centred family planning in the era of FP2020 - Alice Witt; Eloisa Montt-Maray; Marieme Fall; Elizabeth Larson; Nour Horanieh; Nour Horanieh (Frontiers Media S.A., 2023)
The 1994 International Conference on Population and Development was a landmark moment for the international family planning community, who committed to adopt a women-centred approach to programming-one that would prioritise the reproductive and contraceptive intentions, or autonomy, of individuals over population-level demographic concerns. The FP2020 partnership, established in 2012 and lasting until 2020, also described itself using women-centred language. However, throughout the period of FP2020, critics questioned the extent to which women-centred principles truly defined why family planning programmes were funded and how they were implemented. In this study, we use thematic discourse analysis to examine six major international donors' rationale(s) for funding family planning and the measurements they used to articulate successful programming. We present an overview of the rationales and measurements used by all six donors before offering four case studies to demonstrate divergences in their approaches. Our analysis demonstrates that, although donors described the importance of family planning for fostering women's autonomy and empowerment, they also justified family planning on the basis of demographic concerns. In addition, we identified a misalignment between how donors described family planning programmes-using the language of voluntarism and choice-and how they measured their success-through increased uptake and use of contraceptive methods. We call on the international family planning community to reflect on their true motives for funding and implementing family planning and engage in radically rethinking how they capture programme success, in order to better align their rhetoric with their practice.